The Effect of Business Unit, Production, Private Investment, and Minimum Wage on the Labor Absorption in the Large and Medium Industry 6 Provinces in Java Island - Dini Amalia; Nenik Woyanti (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2020)
Industry sectors in Java Island viewed as high productivity sector, therefore high value-added will be generated from the advantage of this industry that will eventually fastened the creation of economical prosperity. Large and medium Industry have potency to become the most contributed sector on labor absorption of manpower. The purpose of this study was to analyze mapping of Labor absorption in the large and medium industry using Klassen typology analysis and determine the effect of variable Large and Medium Industry, Production Value, Private Investment, and Regional Minimum Wage on employment large and medium industry 6 provinces in Java Island for years 2008-2017. This research is using Klassen Typology and Panel data analysis with Fixed Effect Model (FEM). The result of Klassen typology Analysis indicate, there are 2 provinces in Quadrant I, 1 province in Quadrant II, 1 province in Quadrant III, and 2 provinces in Quadrant IV. The Panel data result shows that Large and Medium Industrial unit and Private Investment have positive and significant impact, while Production Value and Regional Minimum Wage have positive and non significant impact on Labor absorption in the Large and Medium Industry 6 provinces in Java Island for years 2008-2017.